2018
DOI: 10.1016/j.bmcl.2018.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Halogenase engineering and its utility in medicinal chemistry

Abstract: Halogenation is commonly used in medicinal chemistry to improve the potency of pharmaceutical leads. While synthetic methods for halogenation present selectivity and reactivity challenges, halogenases have evolved over time to perform selective reactions under benign conditions. The optimization of halogenation biocatalysts has utilized enzyme evolution and structure-based engineering alongside biotransformation in a variety of systems to generate stable site-selective variants. The recent improvements in halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 74 publications
(117 reference statements)
0
31
0
Order By: Relevance
“…Group F can be distinguished into free-substrate halogenases and carrier protein-bound substrate halogenases, which also form separate clades in a phylogenetic tree ( Table 4 ) [ 191 , 192 ]. An increasing interest in these halogenating enzymes is underlined by several reviews in recent years [ 191 , 193 , 194 , 195 , 196 ]. Here, a general overview of flavoprotein halogenases is presented and novel biotechnological aspects are outlined.…”
Section: Two-component Fad-dependent Monooxygenase Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group F can be distinguished into free-substrate halogenases and carrier protein-bound substrate halogenases, which also form separate clades in a phylogenetic tree ( Table 4 ) [ 191 , 192 ]. An increasing interest in these halogenating enzymes is underlined by several reviews in recent years [ 191 , 193 , 194 , 195 , 196 ]. Here, a general overview of flavoprotein halogenases is presented and novel biotechnological aspects are outlined.…”
Section: Two-component Fad-dependent Monooxygenase Systemsmentioning
confidence: 99%
“…Several approaches addressed the improvement of the stability and substrate preference of the halogenases. It was shown that engineering of halogenases can alter the regioselectivity [ 196 , 203 , 222 , 223 , 241 , 242 , 243 ] and expand the substrate scope of these enzymes [ 190 , 196 , 203 , 236 , 242 , 243 , 244 ]. Similar to group E monooxygenases, it was possible to create functional fusion proteins of halogenase and reductase [ 245 ].…”
Section: Two-component Fad-dependent Monooxygenase Systemsmentioning
confidence: 99%
“…It is also worth mentioning the bacterial flavo-halogenases that generate a reactive hypohalous ion to chlorinate and brominate electronrich substrates (van Pée and Patallo, 2006;Payne et al, 2016). Improvement of the aforementioned in planta halogenation of indole alkaloids (Runguphan et al, 2010) could lead to promising new therapeutics, as it is estimated that one-third of the drugs in clinical trials are halogenated (Fraley and Sherman, 2018), and the presence of halogens can significantly enhance drug potency (Imai et al, 2008;Gillis et al, 2015).…”
Section: Flavin Monooxygenasesmentioning
confidence: 99%
“…[8,9] Flavin-dependent halogenases (FDHs), which can regioselectively halogenatea romatic substrates using only halide ion and O 2 ,h avee merged as a new environmentally friendly method for aryl halide synthesis. [10][11][12][13][14][15] FDHsa re closely relatedt of lavin-dependent two-component monooxygenases [16][17][18][19] and consist of two proteins:a halogenase (which convertsO 2 and halide ion into HOCl or HOBr and water with the oxidation of FADH 2 to FAD) and a smaller flavin reductase component (which reduces FADt o FADH 2 using NADH). FDHs have been discovered in the biosynthetic pathways of bacterial and fungal natural products, where they insert chlorine or brominei nto free or acyl carrier protein-bounda romatic substrates.…”
mentioning
confidence: 99%
“…Because of the potential synthetic applications fore nzymecatalyzed regioselective aryl halide synthesis, many groups are engineering FDHs with improved stabilityand catalytic efficiency andw ith altered substrate specificity or regioselectivity for synthetic applicationsa nd generation of novel natural product analogues. [14,15,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] The goal of developing biocatalystsw ith the necessary stabilityf or industrial scale bioconversions has motivated the identification of ah alogenase from at hermophilic bacterium, [41] as well as the engineering of thermostable RebH mutants. [59] To further expand the FDH toolkit, we have expresseda nd purified the halogenase BorH along with its flavin reductase BorF,v erifiedi ts regioselectivity for Trph alogenation, and shown that it is able to chlorinatea nd brominate av arietyo f aromatics ubstrates.…”
mentioning
confidence: 99%